0424 Influence of daytime napping on the discrepancy between subjective and objective nighttime sleep measures in pregnant women with insomnia. (25th May 2022) - Badon, Sylvia; Dietch, Jessica; Gumport, Nicole; Simpson, Norah; Manber, Rachel
Abstract: Introduction: Previous research has documented a tendency among adults with insomnia to underestimate nighttime sleep duration compared to actigraphy estimates. We examined whether discrepancy in nighttime sleep parameters is impacted by daytime napping behavior. Methods: We used baseline data from a randomized controlled trial of insomnia treatment during pregnancy for this cross-sectional analysis (n=97). Women self-reported daytime napping and nighttime sleep characteristics using a 7-day sleep diary and wore an Actiwatch 2 during the same 7-day period. Two women napped daily and were excluded from this analysis. The remaining sample was categorized as intermittent nappers [naps on some but not all days; n=62 (65%)] or non-nappers [no naps on any days; n=33 (35%)]. We summarized daily discrepancy between self-reported and actigraphy-measured nighttime sleep duration and efficiency by daytime napping behavior using means and t-tests. Results: Intermittent nappers provided data for 130 days with naps and 260 days without naps. Non-nappers provided data for 198 days. Among intermittent nappers, there was no meaningful subjective-objective discrepancy for nighttime sleep duration or efficiency (mean discrepancy=1 minute for duration; -0.4% for efficiency); this did not differ between days with naps and days without naps (p=0.98 for sleep duration; p=0.33 for sleep efficiency). Among non-nappers, subjective-objective discrepancy was present (intermittent nappers vs non-nappers p=0.001 for duration; p=0.04 for efficiency), with self-report underestimating actigraphy-measured nighttime sleep duration by 28 minutes and nighttime sleep efficiency by 3.5%. Conclusion: Pregnant women with insomnia who did not nap tended to underestimate nighttime sleep duration and efficiency compared to actigraphy measurement, as has been reported in the general population of adults with insomnia. However, there was no meaningful subjective-objective discrepancy for nighttime sleep duration and efficiency among those who napped intermittently, regardless of that day's napping behavior. It is possible that daytime napping impacts overall accuracy of perceived nighttime sleep. However, because some people with insomnia are unable to nap even when given the opportunity, it is possible that not napping and sleep discrepancy share a common underlying cause. Future research is needed to test if results replicate to non-pregnant populations and explore mechanisms that may explain these findings. Support (If Any): National Institutes of Health (K99HD100585, R01NR013662)